Ambidextrous Leadership among Student Entrepreneurs: Navigating Entrepreneurial and Academic Demands - Adha, Maulana Amirul; et al. (European Journal of Social Science Education and Research, 2026)
This study investigates how student entrepreneurs in Indonesian higher education navigate entrepreneurial and academic responsibilities through the perspective of ambidextrous leadership. The study employed a qualitative Interpretative Phenomenological Analysis (IPA) approach involving 15 student entrepreneurs, four entrepreneurship lecturers, and three business partners selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis. The findings reveal that student entrepreneurs experienced tensions related to innovation and operational stability, uncertainty and competing demands, as well as emotional and psychological pressures resulting from the simultaneous management of academic and business obligations. To respond to these challenges, participants adopted ambidextrous leadership behaviours by balancing flexibility and control while developing adaptive decision-making strategies. The study further found that entrepreneurial experiences contributed not only to business-related competencies but also to the development of entrepreneurial resilience, leadership confidence, emotional maturity, and strategic adaptability. In addition, the findings highlight the importance of experiential learning, adaptive leadership, and supportive higher education environments in helping student entrepreneurs navigate increasingly complex academic, entrepreneurial, and socio-economic challenges.